2021
DOI: 10.1002/adma.202100983
|View full text |Cite
|
Sign up to set email alerts
|

Tough‐Hydrogel Reinforced Low‐Tortuosity Conductive Networks for Stretchable and High‐Performance Supercapacitors

Abstract: All‐solid‐state supercapacitors are seeing emerging applications in flexible and stretchable electronics. Supercapacitors with high capacitance, high power density, simple form factor, and good mechanical robustness are highly desired, which demands electrode materials with high surface area, high mass loading, good conductivity, larger thickness, low tortuosity, and high toughness. However, it has been challenging to simultaneously realize them in a single material. By compositing a superficial layer of tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…Induced by the Hofmeister effect, crystal domains and numerous hydrogen bonds are formed in the hydrogel network, resulting in the high mechanical strength of the all-wood hydrogels [ 35 , 38 , 47 49 ]. The effects of lignin content, PVA content, and salting time on the tensile strength of all-wood hydrogels in the L-directional are further investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Induced by the Hofmeister effect, crystal domains and numerous hydrogen bonds are formed in the hydrogel network, resulting in the high mechanical strength of the all-wood hydrogels [ 35 , 38 , 47 49 ]. The effects of lignin content, PVA content, and salting time on the tensile strength of all-wood hydrogels in the L-directional are further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent mechanical properties of allwood hydrogels are mainly attributed to the strong hydrogen bonding, physical entanglement, and van der Waals forces between cellulose nanofibers, lignin molecules, and PVA chains, and the toughening effect of cellulose nanofibers. Induced by the Hofmeister effect, crystal domains and numerous hydrogen bonds are formed in the hydrogel network, resulting in the high mechanical strength of the allwood hydrogels [35,38,[47][48][49]. The effects of lignin content, PVA content, and salting time on the tensile strength of all-wood hydrogels in the L-directional are further 1 3 investigated.…”
Section: Simultaneous Strengthening and Toughening Of All-wood Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various definition and measurements of tortuosity have been reported from the perspective of engineers geologists and chemists, [34,35] but rarely studied for hydrogels. In fact, hydrogels with low tortuosity are desired for supercapacitors [36] and ion-based bioelectronic devices, so the investigation on the hydrogel tortuosity is in demand. Figure 4l shows the definition of tortuosity: the ratio of the actual distance that ions travel between two points by following the microchannel of the hydrogel to the straight-line distance between the two points (Equation 8).…”
Section: 𝛿 =mentioning
confidence: 99%
“…Recent studies have demonstrated that aligning internal constructions and creating available pore channels for lower tortuosity can effectively regulate the ion transport. [19][20][21][22] Taking these advances, greatly improved device performance has been achieved with high mass loading electrode. However, such achievements can only be valid for specific materials and special equipment, and do not apply to flexible electrodes.…”
mentioning
confidence: 99%